(untitled) (Research, Society and Development, 2020)
The formation of the mathematics teacher is the target of different investigations and criticisms. Some studies detail the exacerbated technical training, others the lack of connection with the practice. Based on such aspects, STS Education (Science, Technology and Society) and Critical Mathematical Education present themselves as possible ways to use Mathematics consciously and that helps in understanding the environment and in decision-making. In this context, the guiding question of this work investigates whether: Are there any similarities between the official documents that guide the Teacher Education courses in Mathematics and the theoretical assumptions of STS Education and Critical Mathematical Education? To answer this question, we set ourselves the objective of analyzing the Mathematics Teacher Training based on an analysis of the guiding documents for the construction of the curricula of the Mathematics Degree Courses, namely, the CNE / CES Opinion 1.302 / 2001, which defines the Guidelines National Curricula for Mathematics, Bachelor and Licentiate Courses and Resolution CNE / CES 3, of February 18, 2003, which establishes the Curriculum Guidelines for Mathematics courses, both public documents available on the website of the Ministry of Education. These were analyzed in the light of the literature that presents STS Education and Critical Mathematical Education. The methodology used is of a qualitative and documentary analysis. The results show that there are explicitly few guidelines in this context, focusing more on the formation of specific themes that are linked to the theme presented in the question that guides the work.